Extramitral Valvular Cardiac Involvement in Patients With Significant Secondary Mitral Regurgitation - Singh Gurpreet K.; Namazi Farnaz; Hirasawa Kensuke; van der Bijl Pieter; van Wijngaarden Aniek L.; Vo N. Mai; Stone Gregg W.; Ajmone Marsan Nina; Delgado Victoria; Bax Jeroen J. (Elsevier Inc., 2022)
Patients with secondary mitral regurgitation (SMR) often have extramitral valve cardiac involvement, which can influence the prognosis. SMR can be defined according to groups of extramitral valve cardiac involvement. The prognostic implications of such groups in patients with moderate and severe SMR (significant SMR) are unknown. A total of 325 patients with significant SMR were classified according to the extent of cardiac involvement on echocardiography: left ventricular involvement (group 1), left atrial involvement (group 2), tricuspid valve and pulmonary artery vasculature involvement (group 3), or right ventricular involvement (group 4). The primary end point was all-cause mortality. The prevalence of each cardiac involvement group was 17% in group 1, 12% in group 2, 23% in group 3%, and 48% in group 4. Group 3 and group 4 were independently associated with all-cause mortality (hazard ratio 1.794, 95% confidence interval 1.067 to 3.015, p = 0.027 and hazard ratio 1.857, 95% confidence interval 1.145 to 3.012, p = 0.012, respectively). In conclusion, progressive extramitral valve cardiac involvement (group 3 and group 4) was independently associated with all-cause mortality in patients with significant SMR.